Multimodality Imaging for Navigation in Endoscopic Transsphenoidal Surgeries - Xu, Yuanzhi; Ni, Jiahua; Bi, Yunke; Zhang, Anke; Xue, Yajun; Qi, Xiangqian; Lou, Meiqing (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims Computed tomography (CT) and magnetic resonance image (MRI) data have been widely used to for navigation in various neurosurgical operations. However, delicate intracranial structures cannot be displayed using only one imaging method. Navigation with multimodality imaging was developed to better visualize these structures in glioma removal, but whether it is useful in endoscopic transsphenoidal surgery is unknown. We describe our clinical experience using multimodality imaging for navigation in endoscopic transsphenoidal surgeries.Material and Methods A total of 134 patients underwent endoscopic transsphenoidal surgery with navigation using multimodality imaging. CT and MR images were fused and processed to optimally visualize anatomical structures of the sphenoidal sinus and tumor.Results Navigation with multimodality imaging offers a precise display of anatomical structures in the sphenoid sinus as compared with navigation based on either CT or MRI.Conclusion Navigation with multimodality imaging is capable of providing optimized guidance during endoscopic transsphenoidal surgeries. The fused images allow precise visualization of sphenoidal sinus structures, lesions and tumors. This is valuable for increasing safety in cases of anatomical variations and potentially decreasing the rate of tumor recurrence.
Keywords: sphenoid sinus; endoscopic transsphenoidal surgery; navigation; multimodality imaging; magnetic resonance image